E0225 Hydrogen sulfide inhabits neurons apoptosis in rats after cardiopulmonary resuscitation. (17th November 2010) - Liao, Xiao-xing; Lin, Ji-yan; Wei, Hong-yan; Li, Hui; Li, Xin; Liu, Rong; Hu, Chun-lin; Huang, Guo-qing; Dai, Gang
Abstract : Objective: To investigate the effects of hydrogen sulfide (H2 S) on brain injury after cardiopulmonary resuscitation (CPR) in rats by examining neurons apoptosis. Methods: The 40 male SD rats were randomly divided into experimental and control groups equally. In control group, CPR was performed with Utstein mode at 6 min after CA. On this basis, sodium hydrosulfide was administrated to the rats after restoration of spontaneous circulation in experimental group. On seventh day after CPR, neurons apoptosis was examined using terminal deoxynucleotidyl transferase mediated dUTP biotin nick end labelling (TUNEL) staining and the expression of caspase-3 was detected by the immunohistochemical strepto avidin biotinperoxidase complex (SABC) method in cortex, hippocampus CA1 region and cerebellum of the rats. Results: 1. There were 12 and 10 rats completed the experiment in the experimental and control group respectively. Their fate between the two groups was no significant difference (χ 2 =0.404, p=0.376). 2. On seventh day after CPR, The serum concentrations of H2 S was 9.12±3.17 μmol/l in the experimental group and the contrast was 3.72±1.05 μmol/l, the difference between the two groups had statistic significance (t=5.136, p=0.000). 3. Compared with the control group, the experimental group's neurons apoptosis index and the sum of integrated optical density (IOD) of caspase-3 in cortex, hippocampus CA1 region and cerebellum were obviously reduced (p<0.05). Conclusion: After CPR, H2 S can inhabit neurons apoptosis and its mechanism may be through caspase-3 pathway. It may play a role in the treatment of the brain injury after CA.